Bimetallic Ir-Sn Non-Carbon Supported Anode Catalysts for PEM Water Electrolysis - Iveta Boshnakova; Elefteria Lefterova; Galin Borisov; Denis Paskalev; Evelina Slavcheva (Inorganics, 2025)
Nanostructured bimetallic IrSn composites deposited on the natural aluminosilicate montmorillonite were synthesized and evaluated as anode electrocatalysts for polymer electrolyte membrane electrolysis cells (PEMECs). The test series prepared via the sol–gel method consisted of samples with 30 wt. % total metal content and varying Ir:Sn ratio. The performed X-ray diffraction analysis and high-resolution transmission electron icroscopy registered very fine nanostructure of the composites with metal particles size of 2–3 nm homogeneously dispersed on the support surface and also intercalated in the basal space of its layered structure. The electrochemical behavior was investigated by cyclic voltammetry and steady-state polarization techniques. The initial screening was performed in 0.5 M H2SO4. Then, the catalysts were integrated as anodes in membrane electrode assemblies (MEAs) and tested in a custom-made PEMEC. The electrochemical tests revealed that the catalysts with Ir:Sn ratio 15:15 and 18:12 wt. % demonstrated high efficiency toward the oxygen evolution reaction during repetitive potential cycling and sustainable performance with current density in the range 140–120 mA cm−2 at 1.6 V vs. RHE during long-term stability tests. The results obtained give credence to the studied IrSn/MMT nanocomposites to be considered promising, cost-efficient catalysts for the oxygen evolution reaction (OER).